Complementarity of formal and informal actors and their networks in support of vulnerable populations in informal settlements: Governance diaries approach - Chumo, Ivy; Kabaria, Caroline; Shankland, Alex; Igonya, Emmy; Mberu, Blessing (Frontiers in Public Health, 2023)
Introduction: Beyond several interests and speculations on the relationship between formal and informal actors and their networks in support of vulnerable populations, most studies do not conclusively establish whether the two types of support are substitutes or complements. While informal care and formal care may be substitutes in general, they are complements among the vulnerable groups. Despite how some studies have described complementarity, further insights on the synergy between formal and informal actors and networks are needed to pinpoint how to maximize policy and interventions to alleviate the challenges of facing marginalised groups in informal settlements. Methods: We conducted an ethnography using governance diaries with 24 participants from Korogocho and Viwandani informal settlements in Nairobi, Kenya. The governance diaries approach involved conducting bi-weekly governance in-depth interviews (IDIs) with study participants for 4 months, complemented with observations, reflections, participant diaries and informal discussions and used content analysis approach for our data analysis. Findings: Informal actors identified include family, neighbors, friends, community groups and community members, and had direct networks. Formal actors on the other hand included government institutions, individuals and authorities that make policies and rules and had desired and possible networks. Both the formal and informal actors and their networks had complementary roles that were both beneficial to the vulnerable populations living and working in informal settlements. The complementarities between formal and informal actors and networks in supporting vulnerable groups were portrayed on roles and responsibilities to the vulnerable groups; rules, regulations and governance in supporting vulnerable groups; knowledge, skills and dynamic workforces among formal and informal actors and their networks; information flow to the vulnerable populations; transition of actors in supporting vulnerable groups availability, access and involvement of formal and informal actors and networks to support vulnerable groups. The complementarities allowed for maximum support of vulnerable populations. Conclusion: We conclude that informal social support is needed regardless of the availability of formal social support. Moreover, a combination of formal and informal actors and related networks are essential to support vulnerable persons. Formal actors should establish, support, or maintain the informal actors and related networks through goodwill.